Apakah Kematangan Emosi mempengaruhi Perilaku Agresi pada Orangtua saat Mendampingi Anak selama Pembelajaran Jarak Jauh? - Nurfitri, Malida; Rahardjo, Wahyu (Psychopreneur Journal, 2023)
Aggression behavior in parents needs to be considered to avoid violence in children, one of which affects aggression behavior is emotional maturity in parents. This study aims to examine whether emotional maturity influences parents' aggressive behavior when accompanying children during PJJ. Respondents in this study were 113 parents who accompanied children aged 5-8 years, parents aged at least 20 years, and located in JABODETABEK. This study used the aggression behavior scale from Buss and Perry (1992) and the emotional maturity scale from Singh and Barghava (1990), both of which were modified by the researcher. This study uses the linear regression method to test the influence between emotional maturity and aggression behavior. The results of this study indicate that there is an influence between emotional maturity and aggression behavior in parents when accompanying children during PJJ with the results of R2 = 0.422 and contributed an influence of 42.3%. This means that showing the emotional maturity of individuals will affect aggressive behavior.